Factors associated with multiple barriers to access to primary care: an international analysis - L. Corscadden; J. F. Levesque; V. Lewis; E. Strumpf; M. Breton; G. Russell (BMC, 2018)
Abstract Background Disparities in access to primary care (PC) have been demonstrated within and between health systems. However, few studies have assessed the factors associated with multiple barriers to access occurring along the care-seeking process in different healthcare systems. Methods In this secondary analysis of the 2016 Commonwealth Fund International Health Policy Survey of Adults, access was represented through participant responses to questions relating to access barriers either before or after reaching the PC practice in 11 countries (Australia, Canada, France, Germany, Norway, the Netherlands, New Zealand, Sweden, Switzerland, the United Kingdom, and United States). The number of respondents in each country ranged from 1000 to 7000 and the response rates ranged from 11% to 47%. We used multivariable logistic regression models within each of eleven countries to identify disparities in response to the access barriers by age, sex, immigrant status, income and the presence of chronic conditions. Results Overall, one in five adults (21%) experienced multiple barriers before reaching PC practices. After reaching care, an average of 16% of adults had two or more barriers. There was a sixfold difference between nations in the experience of these barriers to access. Vulnerable groups experiencing multiple barriers were relatively consistent across countries. People with lower income were more likely to experience multiple barriers, particularly before reaching primary care practices. Respondents with mental health problems and those born outside the country displayed substantial vulnerability in terms of barriers after reaching care. Conclusion A greater understanding of the multiple barriers to access to PC across the stages of the care-seeking process may help to inform planning and performance monitoring of disparities in access. Variation across countries may reveal organisational and system drivers of access, and inform efforts to improve access to PC for vulnerable groups. The cumulative nature of these barriers remains to be assessed.